The Impact Of Fuel Price Fluctuation And Macroeconomic Variables To Airlines Performance - Piranti, Mitra (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The airlines industry is facing significant financial risks which arises from the changes in current economic conditions that has impacted the vulnerability of stock returns as well as its financial performance. This research primarily aims to study the effects of fuel price fluctuations and macroeconomic variables to airlines performance from both internal (represented by RoA and RoE) and market perspective (represented by airlines stock return). Data was obtained from publicly listed airlines registered in the International Air Transport Association (IATA) with their business model classification: Low-Cost Carriers (LCC) and Full-Service Carriers (FSC). The analysis was carried out using multiple panel data regression model.